Development of Long-Duration Energy Storage Projects in Electric Power Systems in the United States: A Survey of Factors Which Are Shaping the Market - Helman, Udi; Kaun, Ben; Stekli, Joseph (Frontiers in Energy Research, 2020)
[NEW ABSTRACT IN SUBMITTED FINAL DOCUMENT] While long duration energy storage is increasingly a topic of interest in the energy community, there has been limited study the value it may capture if and when numerous short duration storage assets, or other assets that can provide energy services, are deployed along side it. The first section of this manuscript provides background on the current distribution of energy storage around the United States and selected literature review relevant to this article. The next four sections focus on each primary category of storage service and examine the evidence on potential for short- and long-duration storage, as well as on the expected penetration of these types of storage over the next decade. The sixth section briefly notes the other clean energy resources which provide flexibility that may compete with storage. The seventh section examines how different policies are driving the market for short- and long-duration storage, and including different types of long-duration storage. This is followed by conclusions and researchable topics.